Low-Voltage-Ride-Through control of a modular multilevel SDBC inverter for utility-Scale photovoltaic systems - Sochor P.; Akagi H.; Tan N.M.L. (Institute of Electrical and Electronics Engineers Inc., 2023)
Bridge circuits; DC-DC converters; Energy conversion; HVDC power transmission; Photovoltaic cells; Renewable energy resources; Cascaded H-bridge inverters; Delta-configured; Low-voltage ride-through; Negative-sequence currents; Photovoltaic systems; Photovoltaics; Renewable energy source; Zero sequence current; Electric inverters